Nanopore sequencing of clonal IGH rearrangements in cell-free DNA as a biomarker for acute lymphoblastic leukemia - Sampathi, Shilpa; Chernyavskaya, Yelena; Haney, Meghan G.; Moore, L. Henry; Snyder, Isabel A.; Cox, Anna H.; Fuller, Brittany L.; Taylor, Tamara J.; Yan, Donglin; Badgett, Tom C.; Blackburn, Jessica S. (Frontiers in Oncology, 2022)
Background Acute Lymphoblastic Leukemia (ALL) is the most common pediatric cancer, and patients with relapsed ALL have a poor prognosis. Detection of ALL blasts remaining at the end of treatment, or minimal residual disease (MRD), and spread of ALL into the central nervous system (CNS) have prognostic importance in ALL. Current methods to detect MRD and CNS disease in ALL rely on the presence of ALL blasts in patient samples. Cell-free DNA, or small fragments of DNA released by cancer cells into patient biofluids, has emerged as a robust and sensitive biomarker to assess cancer burden, although cfDNA analysis has not previously been applied to ALL. Methods We present a simple and rapid workflow based on NanoporeMinION sequencing of PCR amplified B cell-specific rearrangement of the (IGH) locus in cfDNA from B-ALL patient samples. A cohort of 5 pediatric B-ALL patient samples was chosen for the study based on the MRD and CNS disease status. Results Quantitation of IGH-variable sequences in cfDNA allowed us to detect clonal heterogeneity and track the response of individual B-ALL clones throughout treatment. cfDNA was detected in patient biofluids with clinical diagnoses of MRD and CNS disease, and leukemic clones could be detected even when diagnostic cell-count thresholds for MRD were not met. These data suggest that cfDNA assays may be useful in detecting the presence of ALL in the patient, even when blasts are not physically present in the biofluid sample. Conclusions The Nanopore IGH detection workflow to monitor cell-free DNA is a simple, rapid, and inexpensive assay that may ultimately serve as a valuable complement to traditional clinical diagnostic approaches for ALL.